2009
DOI: 10.2139/ssrn.1341380
|View full text |Cite
|
Sign up to set email alerts
|

Subgroup Analysis via Recursive Partitioning

Abstract: Subgroup analysis is an integral part of comparative analysis where assessing the treatment effect on a response is of central interest. Its goal is to determine the heterogeneity of the treatment effect across subpopulations. In this paper, we adapt the idea of recursive partitioning and introduce an interaction tree (IT) procedure to conduct subgroup analysis. The IT procedure automatically facilitates a number of objectively defined subgroups, in some of which the treatment effect is found prominent while i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
404
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(406 citation statements)
references
References 20 publications
1
404
1
Order By: Relevance
“…(Instead of personalizing predictions for each individual, this approach only provides treatment effect estimates for leaf-wise subgroups whose size must grow to infinity.) Other related approaches include those of Su et al [2009] and Zeileis et al [2008], which build a tree for treatment effects in subgroups and use statistical tests to determine splits; however, these papers do not analyze bias or consistency properties.…”
Section: Related Workmentioning
confidence: 99%
“…(Instead of personalizing predictions for each individual, this approach only provides treatment effect estimates for leaf-wise subgroups whose size must grow to infinity.) Other related approaches include those of Su et al [2009] and Zeileis et al [2008], which build a tree for treatment effects in subgroups and use statistical tests to determine splits; however, these papers do not analyze bias or consistency properties.…”
Section: Related Workmentioning
confidence: 99%
“…Develop new and novel methods to identify multiple participant characteristics or clusters of moderators that would identify who is most or least likely to benefit. [94][95][96] 2. To apply individual participant data meta-analysis to homogenous pooled datasets as this would improve statistical power.…”
Section: Summary Of Reviewsmentioning
confidence: 99%
“…They are the interaction tree (IT) and subgroup identification based on a differential effect search (SIDES). 94,96 These methods were initially developed and implemented in a single trial setting. Therefore, they have to be extended so that they can be applied in an individual participant data (IPD) meta-analyses framework.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason why we compare our sHinge method with the ROWSi is that Xu et al (2015) showed by simulation that the ROWSi was superior over the method solving (9) with h k replaced by the hinge loss, which was proposed in Zhao et al (2012) except that LASSO penalty instead of L 2 penalty was used for variable selection. Xu et al (2015) also showed by simulation that ROWSi was superior over other four recently proposed methods, the interaction tree by Su, Tsai, Wang, Nickerson, and Li (2009), the virtual twins by Foster, Taylor, and Ruberg (2011), the logistic regression with LASSO penalty by Qian and Murphy (2011), and the FindIt by Imai and Ratkovic (2013).…”
Section: Simulation Resultsmentioning
confidence: 89%